21st century skills - the needed skills now / Azfahanee Zakaria, Syed Mohammed Alhady Syed Ahmad Alhady and Sarah Sabir Ahmad - Zakaria, Azfahanee; Syed Ahmad Alhady, Syed Mohammed Alhady; Sabir Ahmad, Sarah (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
At present, the world has changed at a turbo speed. The same thing which was done 20 years ago, has definitely been done differently now. The era of globalization, technological innovation, change in climate and demographic have given a great impact on how things were before. For example, the introduction of Facebook by Mark Zuckerberg and Dustin Moskovitz in 2004 has changed the way people socialize and whom they socialized with. The socialization network is now wider and the communication is now way faster than before. Besides that, globalization and technological innovation has resulted in the transformation of work nature itself which leads to new demands and opportunities. With latest hit of COVID 19 in year 2020, the world and its daily activities are definitely not the same any longer. Therefore, to stay competitive in the job market and to remain relevant, the set of skills which a person acquired needs to be upgraded and changed as well. The new set of skills needed are known as the 21st Century Skill (Bruno [n.d]).